An Investigation on Adhesion Behavior of Solid Particles in Water Contaminated Wheel-Rail Contact - Daniel Kvarda; Radovan Galas; Milan Omasta; Martin Hartl (Proceedings, 2018)
The objective of this study was to investigate the influence of solid particles of talc in water contaminated wheel-rail contact. The main aim was to identify situations where low adhesion can occur and define properties that impact the drop of adhesion. For the purpose of this study a laboratory ball-on-disc device was used.